Difference in acceleration patterns in two start techniques: crouch and standing starts - Shinohara, Y.; Nagahara, R.; Matsuo, A.; Maeda, M. (ISBS Proceedings Archive (Michigan), 2018)
The purpose of this study was to investigate the difference in the acceleration patterns between the crouch and standing starts. Ten male sprinters performed two maximal effort 60-m sprints from each of two start techniques. Step-to-step spatiotemporal variables and ground reaction forces over the 50-m distance were measured using 54 force platforms. The current results showed that, when compared variables at each step, the crouch start showed shorter block clearing time, higher running speed through higher step frequency during the second half of the acceleration phase, and more horizontally oriented ground reaction force than standing start. These findings suggest that change in start techniques may alter the acceleration pattern through changes in block clearance time, step frequency and force application technique.